ANALISIS TEKNO-EKONOMI SISTEM PEMBANGKIT HIBRID STUDI KASUS KEPULAUAN MENTAWAI - Altajim, Fauzan Aiman; Utomo, Teguh; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
Indonesia's electricity generation still predominantly uses non-renewable sources, while renewable energy sources are still minimal. This study focuses on the Mentawai Islands which rely on Diesel Power Plants (PLTD) with high fuel costs. This research analyzes the good potential for Hybrid Power Plants (PLTH), combining solar and diesel energy to meet 24-hour electricity needs in rural areas. Research methods in techno-economic analysis involve data collection, determining specifications for Solar Power Generation Systems (PLTS), designing PLTH systems, and simulations using Homer software. This research shows that PLTH produces 6,034,395 kWh/year, with 3.36% PLTS penetration. The cost per kWh (COE) of PLTH is IDR 4,198.50. This research highlights the potential of PLTH as an effective and sustainable energy solution in the Indonesian archipelago. Keywords: PLTH, PLTD, PLTS, Output Power